2010
DOI: 10.3168/jds.2009-2413
|View full text |Cite
|
Sign up to set email alerts
|

The effect of storage temperatures and packaging methods on properties of Motal cheese

Abstract: The effects of storage temperature (+4 degrees C and -18 degrees C) and packaging method (nonvacuum and vacuum) on biogenic amines in Motal cheese during storage periods were investigated. In addition, dry matter, titratable acidity, total nitrogen, water-soluble nitrogen, trichloroacetic acid-soluble nitrogen, phosphotungstic acid-soluble nitrogen, free amino group (proteolysis), electrophoretic patterns of casein, and amounts of lactic acid bacteria and coliforms were determined. Storage period had a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…The presence of BAs in different types of cheese has been described in a lot of surveys. More than 15 BAs have been analyzed [5,9,37,[43][44][45][46][47]. Among different types of cheese; cadaverine was found to be more dominant than other BAs.…”
Section: Biogenic Amines In Dairy Productsmentioning
confidence: 99%
“…The presence of BAs in different types of cheese has been described in a lot of surveys. More than 15 BAs have been analyzed [5,9,37,[43][44][45][46][47]. Among different types of cheese; cadaverine was found to be more dominant than other BAs.…”
Section: Biogenic Amines In Dairy Productsmentioning
confidence: 99%
“…A step further, frozen temperature (e.g., −18°C) impairs the increase on the BA accumulation, most likely because the microbial activity is stopped (Andiç et al, 2010). However, more affordable solutions have to be found.…”
Section: Factors Influencing Biogenic Amine Production In Dairy Productsmentioning
confidence: 99%
“…1). Previously, it was shown that low pH (e.g., 4.0e5.5) favours generation of BAs, because FAA decarboxylation is part of microbial cell response to acid stress, which allows the consumption of intracellular protons (Andiç, Gençcelep, Tunçtürk, & K€ ose, 2010;Fernandez et al, 2007;Marcobal, Martin-Alvarez, Moreno-Arribas, & Muñoz, 2006).…”
Section: Discussionmentioning
confidence: 99%